Description and performance analysis of a flexible photovoltaic/thermal (PV/T) solar system. (July 2019) - Gagliano, Antonio; Tina, Giuseppe M.; Nocera, Francesco; Grasso, Alfio Dario; Aneli, Stefano
Abstract: The main objectives of the present paper are to describe a pilot cogenerative PV/T plant and discuss its preliminary electrical and thermal experimental data. The PV/T plant is installed in the campus of the University of Catania, (Catania, Italy) on the eastern coast of Sicily, right in the centre of the Mediterranean area. The operative conditions of the experimental PV/T plant can be modified to implement parallel and series electrical and hydronic connections to the PV/T modules. The electrical and thermal load supplied by the PV/T plant can also be managed in order to simulate different energy demand scenarios. This study reports the main thermal and electrical operating parameters of the PV/T plant on the basis of experimental measurements, with the PV/T modules connected in series. A good level of correspondence was found between the measurements and the simulations obtained from a model of the system, particularly as regards electrical features.